2016
DOI: 10.1021/acsami.6b07403
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Triggered and Thermally Reconfigurable Shape Memory Graphene-Vitrimer Composites

Abstract: Conventional thermoset shape memory polymers can maintain a stable permanent shape, but the intrinsically chemical cross-linking leads to shape that cannot be altered. In this paper, we prepared shape memory graphene-vitrimer composites whose shape can be randomly changed via dynamic covalent transesterification reaction. Consecutive shape memory cycles indicate stable shape memory with undetected strain shift and constant shape fixity and recovery values (Rf > 99%, Rr > 98%). Quantitative characterization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
163
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(167 citation statements)
references
References 35 publications
4
163
0
Order By: Relevance
“…CNTs have been successfully used to assist self‐healing of vitrimers through near infrared absorption. The CNT loading used in this study is the lowest by comparison with data reported in literature . In addition, the dual exchange reactions in this vitrimer system allowed for better recovery of mechanical properties.…”
Section: Selected Fast Self‐healing Systems For Mechanical Property Rmentioning
confidence: 72%
See 1 more Smart Citation
“…CNTs have been successfully used to assist self‐healing of vitrimers through near infrared absorption. The CNT loading used in this study is the lowest by comparison with data reported in literature . In addition, the dual exchange reactions in this vitrimer system allowed for better recovery of mechanical properties.…”
Section: Selected Fast Self‐healing Systems For Mechanical Property Rmentioning
confidence: 72%
“…In this case, organoaniline absorbed NIR and produced the required heat for self‐healing. Due to the high NIR absorbance capability of nanotubes and graphene nanoplatelets, they are used in vitrimers to generate the heat required for activation of the exchange reactions. Using small amounts of carbon nanotubes or graphene nanoplatelets decreased the healing time significantly.…”
Section: Selected Fast Self‐healing Systems For Mechanical Property Rmentioning
confidence: 99%
“…Also, transesterification-based shape memory composites based on graphene-filled vitrimers were prepared. [35] However, all of these approaches implement the DCC throughout the resin and fail to implement the desired DCC at the polymer–matrix interface where stress is concentrated, contributing to composite failure.…”
Section: Introductionmentioning
confidence: 99%
“…Vitrimers belong to the second category of CANs in which the crosslinking bonds have an associative nature resulting in the ability of the material to change its topology via exchange reactions. These reactions normally are triggered by heat, which causes the gradual decrease in system viscosity with increasing temperature and provides malleability to the network.…”
mentioning
confidence: 99%
“…Since vitrimerization also allows for the processing of a thermoset just like a thermoplastic, it affords the unique advantage of incorporating fillers into the thermoset network during recycling to compensate for the drop in mechanical properties due to the catalyst. The addition of fillers to enhance the properties of vitrimers has already been studied extensively . Just as an example, 10 wt% of highly branched carbon nanotubes with a diameter of 7–9 nm known as carbon nanostructures (CNS) were extruded along with the vitrimerized PU samples with the same parameters mentioned above and tested for mechanical properties as can be seen in Figure c.…”
mentioning
confidence: 99%